ECONOMICAL TERMS AND THEIR USE IN TERMINOLOGY SYSTEM - Khaitova Gulshan Bahodirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Political and social transformations in the life of Russia in the early 90s of the 20th century led to certain changes in the lexical system of the Russian language, which quickly responded to the new needs of society. Most key economic terms come out of their narrow sphere of use and are mastered in general literary language. The loss of terminology by terms and the transition to the sphere of general use indicates the increasing involvement of a person in the field of economic interests and his dependence on economic processes.